NGUỒN GỐC VÀ ĐIỀU KIỆN THÀNH TẠO CỦA CORINDON TRONG ĐÁ GNEIS MỎ TRÚC LÂU, HUYỆN LỤC YÊN, TỈNH YÊN BÁI - Thuyết, Nguyễn Thị Minh; Nhung, Ngụy Tuyết; Khôi, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2011)
Origin and forming conditions of corundums in gneiss in Truc Lau mine, Luc Yen District, Yen Bai ProvinceTruc Lau gem mining area, belonged to Truc Lau, Phuc Loi commune of Luc Yen district, Yen Bai province, islocated in the Red River zone. Here, corundums (ruby, sapphire) have been exploited in placer since the late 80s of the last century. In recent years, they have been found in gneiss host rock. Based on the results of chemical composition, crystal structure, inclusion, color, absorption spectrum of corundum as well as mineral assemblage analysis and thermobarometer confirmed that corundums from Truc Lau gneiss are the production of metapelite and formed by breaking down of muscovite at 650-769oC, 7.6-5.2kbar.